Robust quantitative depth estimation on CFRP samples using active thermography inspection and numerical simulation updating. (April 2017) - Peeters, J.; Ibarra-Castanedo, C.; Sfarra, S.; Maldague, X.; Dirckx, J.J.J.; Steenackers, G.
Abstract: A quantitative evaluation of delaminations in composite laminates encounters multiple difficulties due to the anisotropic behaviour of the laminate. Extensive calibrations for each structure are required and each depth needs certain manual modifications for optimal performance of the estimation routines. In this manuscript, a robust technique is developed using a numerical model to estimate the thermal diffusivity through the anisotropic material which improves defect depth estimation between each layer. Three different calibration depths are necessary to compute the diffusivity through a certain stacking sequence of a multi-layered composite laminate. The results are compared with the state-of-the-arts experimental evaluation techniques and with a regular numerical model. It is seen that especially for deeper defects, the optimised numerical model delivers more accurate results due to the considered anisotropic diffusivity.